THE EFFECT OF MIND MAPPING TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Triana Sari; Sortha Silitonga (Universitas Negeri Medan, 2016)
This study was conducted as an attempt to discover the effect of Mind Mapping Technique on Students’ Achievement in Writing Descriptive Text. It was an experimental research. The subject was students of Grade VIII, Junior High School (SekolahMenengahPertama:SMP), which consisted of 207 students. The research was divided into two groups: experimental and control groups. The instrument used to collect the data was writing descriptive text. To obtain the reliability of the test, the writer applied William Knight formula. The result of the reliability was 0.95, and it was found that the test was reliable. The data were analyzed by using t-test formula. The analysis showed that the scores of the students in the experimental group were significantly higher than the scores of the students in the control group at the level of significant μ= 0.05 with the degree of freedom (Df) 72, t-observed value 3.510 > t-table value 1.9932. The findings indicate that using Mind Mapping Technique significantly affected the students’ writing achievement. So, English teachers are suggested to use Mind Mapping Technique in order to improve students’ writing achievement.